NAWACITA SEBAGAI STRATEGI KHUSUS JOKOWI PERIODE OKTOBER 2014-20 OKTOBER 2015 - Mochdar Soleman; Mohammad Noer (POLITIK, 2017)
idea of Bung Karno about Trisakti is enlarged by Jokowi as the superior strategy; sovereign in 12 programs of political field, self-reliant in 16 programs of economics and personality in 3 programs of culture, by taking into account the contemporary context, hence, it is prioritized 9 (nine) main programs or Nawacita --- as the instruments of operational strategies to become a bigger Indonesia. The content ideas of Nawacita is the economics equity for infrastructure developments as for development dialectics. It is equal to political developments since Old Era, New Era, and Reformation Era. By using qualitative method, political development strategies approaches, and the theory of National interest, hence, it is clearly seen that the political sovereignty created political equity in solving the labors issue and businessman --- to assure the protection of labors and business for the businessman to give their capital investments in domestic due to create liberal economics system and the ideological paradox. Consequently, the economic independence is needed: infrastructure developments as the connector of each island in some areas as the process of central development equity both physical and mental development. As for cultural  personality: to bring back the basic philosophy of Pancasila as the guide of the nation’s development path and character.Keywords: Political developments, Trisakti, & NawacitaGagasan Trisakti Bung Karno, diperluas Jokowi sebagai strategi khusus, yakni berdaulat dalam bidang politik 12 program, berdikari dalam ekonomi 16 program dan berkepribadian dalam budaya 3 program, dengan mempertimbangkan konteks kekinian, maka, diprioritaskan 9 (sembilan) program utama atau Nawacita --- sebagai instrumen langkah-langkah taktis operasional jalan perubahan menuju Indonesia yang lebih besar. Isi gagasan Nawacita adalah pemerataan ekonomi untuk pembangunan infrastruktur sebagai dialektika pembangunan. Hal tersebut selaras dengan pembangunan politik semenjak Orde Lama, Orde Baru, Orde Reformasi. Lewat metode kualitatif dan pendekatan strategi pembangunan politik, serta teori tentang kepentingan nasional, maka, tampak dengan jelas betapa kedaulatan politik melahirkan politik keseimbangan dalam mengatasi masalah buruh dan pengusaha --- untuk memberikan kepastian perlindungan buruh dan kepastian usaha bagi pengusaha menanamkan investasi modalnya di dalam negeri sehingga menimbulkan sistem ekonomi lebih liberal dan terjadi paradoks ideologisasi. Untuk itu, maka, diperlukan kemandirian Ekonomi: pembangunan infrastruktur sebagai penghubung antar pulau-pulau di daerah sebagai proses pemerataan pembangunan pusat dan daerah yang Indonesiasentris baik pembangunan fisik maupun pembangunan mental, sedang pada Kepribadian Budaya: Mengembalikan filosofi dasar atau falsafah dasar kita Pancasila sebagai penuntun jalan pembangunan bangsa dan pembangunan karakter.